2006
DOI: 10.1177/000313480607201007
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Ablation of Hepatic Metastases from Colorectal Cancer: Are Newer Generation Probes Better?

Abstract: Second-generation radiofrequency ablation (RFA) probes and their successors have more power, shorter ablation times, and an increased area of ablation compared with the first-generation probes used before 2000. We examined whether the use of the newer probes has improved the clinical outcome of RFA for hepatic metastases of colorectal cancer at our tertiary cancer center. Of 160 patients who underwent RFA between 1997 and 2003, 52 had metastases confined to the liver: 21 patients underwent 46 ablations with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…These studies should be interpreted with caution as they have considerable heterogeneity, with variations in the technical radiofrequency approach (percutaneous, laparoscopic or open) and with the type of RFA probe used (35)(36)(37). Also, these variant RFA approaches are not strictly comparable and each has particular advantages and disadvantages.…”
Section: Resultsmentioning
confidence: 99%
“…These studies should be interpreted with caution as they have considerable heterogeneity, with variations in the technical radiofrequency approach (percutaneous, laparoscopic or open) and with the type of RFA probe used (35)(36)(37). Also, these variant RFA approaches are not strictly comparable and each has particular advantages and disadvantages.…”
Section: Resultsmentioning
confidence: 99%
“…However, a small study (performed laparoscopically) has recently shown that a new, commercially available bipolar system can create ablation zones larger than 10 cm and that this system has allowed for improved local control of tumors ≥3.5 cm 41. In addition, monopolar probes can now ablate areas up to 7 cm 42. The advancement of RFA technology should continue to increase the potential ablation zone and thus the efficacy of the procedure on tumors of larger size.…”
Section: Planningmentioning
confidence: 99%
“…This approach has been used to treat tumors as large at 15 cm 15. Great care and planning are required when creating overlapping spheres as serial ablations may increase the chance of leaving still viable tumor in situ at the peripheral intersections of these overlapping ablation zones 42. The development of a switch‐box that allows the simultaneous use of multiple, electrically independent electrodes by temporally rotating the current through the electrodes has facilitated the creation of overlapping spheres in a single treatment 52, but does not alleviate the challenges in planning and adequately executing such treatments.…”
Section: Monitoring and Controllingmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies indicate that lung tumors are ideal targets for RFA since the surrounding air in the adjacent normal lung parenchyma provides an insulating effect, concentrating the RF energy within the tumor tissue ( 9 ). The major problem with RFA treatment is that thermal destruction may occur before achieving complete tumor destruction ( 10 ). According to a previous study, lung RFA is associated with increased rates of local recurrence in tumors with large volumes since it is difficult to reach sufficiently high temperatures further away from the heat source, particularly in the treatment of larger tumors ( 11 ).…”
Section: Introductionmentioning
confidence: 99%